DEVELOPMENT DRIVERS AND APPLICATION PRACTICE OF HIGH-PRECISION GUIDED MUNITIONS - Rashevskyi, Yevhen; Pantielieieva, Natalia; Khutorna, Myroslava; Goncharenko, Olena (Collection of scientific papers «ΛΌГOΣ», 2025)
High-precision guided munitions (HPGMs) are means of destructive equipped with a control system, high-tech guidance and global positioning systems and/or an integrated inertial navigation system to identify military targets. High-precision guided munitions include tactical missiles, guided missiles, guided munitions (including aircraft bombs), and loitering munitions.